Liquid level control of a couple tank system based on smooth trajectory tracking using PID controller - Salman, Razeni (2009)
Industries such as petro-chemical industries, paper making industries, waste management and others are the vital industries where liquid level and flow control are essential. Liquids will be processed by chemical or mixing treatment in the tanks, but always the level fluid in the tanks must be controlled, and the flow between tanks must be regulated in the presence of nonlinearity and inexact model description of the plant. This project investigates the usage of Proportional-Integral-Derivative (PID) controller in controlling the liquid level in the second tank of Coupled-Tank plant through variable manipulation of water pump in the first tank. This project presents the ability of controlling the liquid level of a coupled tank system that used Programmable Logic Controller (PLC) as a main controller hardware. A PID controller has been developed and designed via ladder programme of CXprogrammer. A mathematical model of the couple tank system was derived by refering to the experimental manual and verified by using MATLAB software. The controller parameters derived from the simulation and design process using MATLAB as well. The project is based on Single Input Single Output (SISO) system which mean the liquid will entering the tank 1 (pump 1) in couple tank while the level control is in tank 2 in the condition of pump 2 is set OFF. The aim of the project is to design controller that can maintain the level and minimize the error (SPCV) value at any of given set point(SP). It is to show that PID controller could produce appropriate control signal to the coupled-tank system and minimize the error value for the system. A series of tracking performance tests conducted to evaluate the controller performance in comparison to other controller such are fuzzy controller, DMRAC controller or other controller that used by other reearcher before. . The outcome of the project reveals that PID controller could carry a small error rate when the appropriate value of Kp, Ki, and K are applied. The framework of this project is generic enough to have an overview of the possible outcome before implementing the PID controller in real-time system in the future.